The development status of rice iron-coated wet direct seeding technology in Japan - Hao, An; Bing, He; Chao, Li; Xiaohang, Wang; Hong, Lang; Shuai, Wang (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
This review examines the development and potential of iron-coated wet direct seeding technology in Japanese rice cultivation, emphasizing its role in mitigating labor shortages and enhancing the sector’s competitiveness. The technology, which has been rapidly adopted, improves seedling emergence, reduces seed drifting, and minimizes damage from birds and rodents by increasing seed weight and hardness. Comprising cost-effective materials such as iron powder and calcium sulfate, the coating process is both straightforward and economical. While some studies report a modest 5 % reduction in yield relative to transplanting, others suggest comparable or even improved yields. The technology offers significant advantages in reducing labor input, lowering production costs, and improving seedling establishment, positioning it as a promising solution not only for Japan but also for other rice-producing regions facing similar challenges.